Toward a broader understanding of stress and coping mixed methods approaches - Collins, Kathleen M.; Onwuegbuzie, Anthony J.; Jiao, Qun G. (Research on stress and coping in education series., 2009)
Research on stress and coping phenomena has been among the most widely studied topics in social and behavioral sciences during the past several decades. Notwithstanding, the authors in this book have expanded the base of stress and coping research by providing a valuable reference source that includes guidelines and frameworks as well as empirical findings related to the application of mixed methods approaches to the study of stress and coping.This book is intended not only for stress and coping researchers, but also for social and behavioral science researchers at various levels--from students, instructors, and advisors to applied researchers, research methodologists, and theorists. The 15 chapters are divided into three distinct sections. The five chapters in Section I focus mainly on topics pertaining to the conceptual and theoretical aspects of mixed methods research in the study of stress and coping. The five chapters in Section II address the major methodological issues of mixed methods research. Section III presents five empirical studies of mixed methods research as applied to the field of stress and coping.This book illustrates the perspectives of innovative interconnections in the application of mixed methods research to the study of stress and coping. It also provides readers with new ways of designing and evaluating strategies and programs that aim to reduce stress and improve coping mechanisms.